Optimalisasi Proses Transportasi Anilin Menggunakan Membran Minyak Nabati dalam Teknik Membran Cair - Refinel; Emil Salim; Ikhsan Gusti Rilma (Departemen Kimia Universitas Andalas, 2023)
Aniline transport using a supported liquid membrane technique has been carried out in the separation of aniline from aqueous solutions. The aniline transport process used vegetable oil as a liquid membrane and ceramics as a support material. The concentration aniline was determined using an UltraViolet-Visible (UV-Vis) Spectrophotometer at a wavelength of 230 nm. Optimal conditions found that a good type of liquid membrane was olive oil, a pH value of 3 in the source phase, the concentration of aniline 12 x 10-5 M, the concentration of HCl 1.0 M, and a stirring time of 90 minutes. Under optimum conditions, the percentage of aniline in the receiving phase was 36.19% and source phase was 1.48%. HCl is not able to attract all the molecules that are in the membrane phase. The receiving compound which has a strong affinity will provide a large amount of transport for the aniline transport process.